2021
DOI: 10.1590/0103-8478cr20200380
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of fishburgers with the addition of different protein sources and taro flour

Abstract: The present study aims to develop Nile tilapia hamburger with incorporation of whey, collagen from chicken feet and taro flour. A complete factorial design 2³ was performed to investigate the influence of the variables on weight loss, shrinkage, color and shear force, that were used to propose mathematical models. Proximate composition, microbiological characteristics and sensory properties were also evaluated. Factors such as taro flour and whey were significant and contributed to a higher yield for fish burg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
1
0
3
Order By: Relevance
“…The moisture found in the burgers in this study was similar to that of fish burgers developed by Maciel et al (2021), with 72%. Fish protein has similar nutritional values to those of bovine protein (Khan et al, 2020;Lee et al, 2019); however, higher values were found in fish burgers when compared to this study (Marconato et al, 2020).…”
Section: Nutritional Composition Of Fish Burgerssupporting
confidence: 74%
“…The moisture found in the burgers in this study was similar to that of fish burgers developed by Maciel et al (2021), with 72%. Fish protein has similar nutritional values to those of bovine protein (Khan et al, 2020;Lee et al, 2019); however, higher values were found in fish burgers when compared to this study (Marconato et al, 2020).…”
Section: Nutritional Composition Of Fish Burgerssupporting
confidence: 74%
“…Marengoni et al (2009) trabalhando com fishburgers de CMS de tilápia encontraram valores próximos ao encontrado estudo para três de suas quatro formulações, 1,73%, 3,79% e 3,86%. Maciel et al (2021) e Bainy et al (2015) relataram valores superiores ao encontrado nesse estudo, 4,19% e 5,21% respectivamente, para fishburgers processados a partir de tilápia do Nilo.…”
Section: Avaliação Microbiológica Da Matéria-primaunclassified
“…Esses ensaios tinham percentuais de umidade inversos, sendo o E1 e A8 ensaios com maior umidade, e consequentemente menores percentuais dos demais componentes. Outros autores relataram valores de 2,48% (ALI et al, 2019), 2,17% (BAINY et al, 2015 -ambos em fishburger de tilápia, 2,1% em fishburger de biquara (Haemulon Plumierii) adicionado de farelo de trigo (RAÚL et al, 2018) e 0,65% em fishburger de tilápia adicionado de diferentes fontes de proteína (MACIEL et al, 2021).…”
Section: Avaliação Microbiológica Da Matéria-primaunclassified
See 1 more Smart Citation
“…In turn, fish processing can provide a range of food products that meet consumers' desires, adding to the fish new characteristics and attributes such as appearance, texture, odor, color, and flavor, in addition to providing better palatability, increasing shelf life, and commercial value (Bombardelli, Syperreck & Sanches, 2005;Hall, 2010). Processing techniques in line with studies on physicochemical properties and optimization models focusing on byproducts and functional ingredients can provide fish products with promising results in terms of sensory quality, cost reduction, and full use of the raw material as a strategy for the reduction of agrifood industry waste, such as the use of Mechanically Separated Meat (MSM) Maciel et al, 2021).…”
Section: Introduction: Overview and Objectivesmentioning
confidence: 99%